Grammatical Intricacy in Product Descriptions and Advertisement Videos: Lesson from IKEA - Tegar Aliansyah; Siti Yuliah (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2023)
This study analyzed grammatical intricacy (GI) found in written and spoken texts represented by 20 product descriptions and 20 advertisement videos of IKEA. The data were collected purposively from IKEAÃ¢â‚¬â„¢s official website and YouTube Channel. The objectives of this study were to investigate the complexity of IKEA product descriptions and advertisement videos using GI and to identify which text has a higher average GI score. This study applied a descriptive qualitative method and formula proposed by Eggins to calculate the complexity of the texts. The analysis process included identifying the clauses and sentences based on Hogue & OshimaÃ¢â‚¬â„¢s theories, counting the number of clauses and sentences, and calculating the GI score. The results showed that (1) product descriptions and advertisement videos composed by IKEA possessed a low level of complexity as the average GI score of both texts is below 2.00. (2) Advertisement videos reach a higher score (1.74) compared to product descriptions (1.57); however, the difference is not significant. The results of this study may contribute to two important implications, both theoretically and practically. Theoretically, the results enrich the knowledge on grammatical intricacy. Practically, this study provides an insight for marketing practitioners to compose marketing discourse with strong messages to lure customersÃ¢â‚¬â„¢ attention.Ã‚Â